Topology authentication for piping isometric drawings. (September 2015) - Su, Zhiyong; Yang, Xin; Liu, Guangjie; Li, Weiqing; Tang, Weiqing
Abstract: Piping isometric drawings, which feature their intrinsical topological relation rather than just geometrical shape, are important industrial art works in the field of Computer-Aided Design (CAD). This paper takes a fresh look at the topology integrity authentication of piping isometric drawings, which has not been mentioned before in the literature, from the digital watermarking perspective. A blind and semi-fragile watermarking based algorithm is proposed to address the referred interesting issue. The topology authentication problem of piping isometric drawings is investigated. In addition to the stretching operation, both global and local similarity transformation operations, which are critical problems in the case of watermarking embedding and extraction, are analyzed in detail. The topological graph is extracted and constructed from the drawing firstly. Then, similarity transformation invariants are constructed as watermarks carriers for each node. After that, the topological relation among joint components is encoded into singular watermarks for each node of the graph. These generated topology sensitive watermarks are embedded into geometrical invariants of each node via quantization index modulation. Theoretical analysis and experimental results demonstrate that our approach yields a strong ability in detecting and locating unauthorized topology attacks while achieves robustness against both global and local similarity transformations especially the stretching operation. The proposed scheme can be employed to authenticate topology integrity for each of the drawings derived from the model individually in industry practices. Highlights: The topology authentication problem of piping isometric drawings is addressed. A semi-fragile watermarking scheme for the topology authentication is proposed. The proposed scheme is robust against local similarity transformations. The proposed scheme is invariant to the stretching operation on pipes. The proposed scheme provides good tamper localization accuracy.